Pengembangan LKPD Berbasis Question Prompt Scaffolding untuk Meningkatkan Scientific Writing Skill Peserta Didik pada Pembelajaran IPA SMP - Fenti Defita Sari; Supeno; Zainur Rasyid Ridlo (Cetta: Jurnal Ilmu Pendidikan, 2023)
In science learning, scientific writing skills are an important aspect that can be an indicator of learning success and are of great benefit for students. In fact, scientific writing skills still need to be improved. So teaching materials are needed that can provide assistance to students to practice their scientific writing skills, one of them is student worksheet based on question prompt scaffolding. The purpose of this study is to describe the validity, practicality, and effectiveness of student worksheet based on the question prompt scaffolding. The type of research used is research and development. The research design used is the ADDIE model which consists of five phase, namely analysis, design, develop, implement, and evaluate. The location where this research was canducted is SMP Negeri 1 Jember. Validity reached a value of 97% which is included in the valid category. Practicality reached a value of 94% which is included in the practical category. Analysis of effectiveness using the N-gain test which obtained an overall average N-gain in laboratory reports 1 and 2 of 0,123 in the low category, and an overall average N-gain in laboratory reports 2 and 3 of 0,301 in the medium category. These results indicate a fairly good increase, from the low to medium category. The students’ response result received a rating of 82.67% in the very good category. Thus, it can be concluded that this student worksheet is valid, practical, and effective in improving students' scientific writing skills in science learning.